Wild massive - Moore, Scotto (A Tordotcom Book, published by Tom Doherty Associates/Tor Publishing Group, 2023)
"Scotto Moore's Wild Massive is a glorious web of lies, secrets, and humor in a breakneck, nitrous-boosted saga of the small rejecting the will of the mighty. Welcome to the Building, an infinitely tall skyscraper in the center of the multiverse, where any floor could contain a sprawling desert oasis, a cyanide rain forest, or an entire world. Carissa loves her elevator. Up and Down she goes, content with the sometimes chewy food her reality fabricator spits out, as long as it means she doesn't have to speak to another living person. But when a mysterious shapeshifter from an ambiguous world lands on top of her elevator, intent on stopping a plot to annihilate hundreds of floors, Carissa finds herself stepping out of her comfort zone. She is forced to flee into the Wild Massive network of theme parks in the Building, where technology, sorcery, and elaborate media tie-ins combine to form impossible ride experiences, where every guest is a VIP, the roller coasters are frequently safe, and if you don't have a valid day pass, the automated defense lasers will escort you from being alive. Wild Massive: The #1 destination for interdimensional war. Rate us on VacationAdvisor!"--